Fissure sealant materials: Wear resistance of flowable composite resins - Sohrab Asefi (Journal of Dental Research, Dental Clinics, Dental Prospects, 2016)
Background. Wear resistance of pit and fissure sealant materials can influence their retention. Wear characteristics of sealant materials may determine scheduling of check-up visits. The aim of this study was to compare wear resistance of two flowable composite resins with that of posterior composite resin materials. Methods. Thirty-five disk-shaped specimens were prepared in 5 groups, including two flowable composite resins (Estelite Flow Quick and Estelite Flow Quick High Flow), Filtek P90 and Filtek P60 and Tetric N-Ceram. The disk-shaped samples were prepared in 25-mm diameter by packing them into a two-piece aluminum mold and then light-cured. All the specimens were polished for 1minute using 600-grit sand paper. The samples were stored in distilled water at room temperature for 1 week and then worn by two-body abrasion test using "pin-on-disk" method (with distilled water under a 15-Nload at 0.05 m/s, for a distance of 100 meter with Steatite ceramic balls antagonists). A Profilometer was used for evaluating the surface wear. Data were analyzed with the one-way ANOVA. Results. Estelite Flow Quick exhibited 2708.9 ± 578.1 μm2 and Estelite Flow Quick High Flow exhibited 3206 ± 2445.1 μm2of wear but there were no significant differences between the groups. They demonstrated similar wear properties. Conclusion. Estelite flowable composite resins have wear resistance similar to nano- and micro-filled and micro-hybrid composite resins. Therefore, they can be recommended as pit and fissure sealant materials in the posterior region with appropriate mechanical characteristics.